Discussing Social Media Using Affordance of Young Chinese Ethnic Minority Group Users - Li, Lifu; Kang, Kyeong (Cultural Arts Research and Development, 2024)
The study explores young Chinese ethnic minority group (EMG) users’ social media using affordance for engagement when they engage in intercultural contact on social media platforms. Grounded on the affordances theory, the relationships between influencing factors and using affordance have been presented in the research framework. Through interviewing fourteen EMG participants, critical findings in this paper have also been discussed in the final section, such as young Chinese EMG users who understand the original language supporting multi-language engagement, focusing on cultural content and following EMG influencers. Based on the comparison among various influencing factors, several suggestions have been provided for social media platform designers and related departments.